Dampak Muatan Etika Dalam Pengajaran Akuntansi Keuangan dan Audit Terhadap Persepsi Etika Mahasiswa yang Dimoderasi oleh Kecerdasan Kognisi dan Kecerdasan Emosional: Studi Eksperimen Semu - Lidya Agustina; Christine Dwi Karya Susilawati (Jurnal Akuntansi, 2012)
Ethics education is more than studying the code of professional conduct, but rather a process whereby individuals become more consciously involved in making ethical decisions (Langenderfer and Rockness:1989). This study investigates whether integrating ethical issues in financial accounting course will improve student’s ethics perception. The research design was quasi experiment, posttest-only control group design, and the subject were students who took intermediate accounting. The hypotheses of this research were: (1) loading ethical issues in financial accounting course influenced student’s ethics perception, and (2) interaction between ethical issues in financial accounting course and student GPA (Grade Point Average) influenced student’s ethics perception. The research hypotheses were tested using two way ANOVA. The result show that: (1) loading ethical issues in financial accounting course not influenced student’s ethics perception, (2) interaction between loading ethical issues in financial accounting course and student GPA significantly influenced the student’s ethics perception. Considering the current climate of good corporate governance, educators can no longer postpone in integrating ethics issues in accounting curriculum.